Biomechanical determinants of volleyball smash performance in physical education: a comprehensive literature review - Delvi Junaidi; Padli Padli (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
Smash performance in volleyball is a complex motor skill influenced by lower-limb explosive power, hand–eye coordination, and trunk flexibility. This systematic literature review (2018–2025) synthesized 15 studies from international and national databases using PRISMA guidelines. Findings indicate that explosive leg strength drives take-off height, angle of attack, and initial momentum, with rate of force development and coordination patterns mediating mid-air stability. Hand–eye coordination critically supports timing accuracy and directional control, while trunk flexibility enables efficient energy transfer and arm acceleration. Effective smash execution emerges from the interaction of force production, neurosensory control, and segmental mobility. Training programs should adopt multidimensional approaches integrating plyometrics, visual-motor drills, and flexibility exercises, tailored to developmental stage and individual needs, with assessments guiding prioritization. Future research should evaluate combined interventions and performance transfer in competitive settings.